Do Higher Temperatures Increase Growth in the Nocturnal Gecko Homonota darwini (Gekkota: Phyllodactylidae)? A Skeletochronological Assessment Analyzed at Temporal and Geographic Scales - Kubisch, Erika Leticia (2012)
Recent studies predict that several lineages of tropical animals are at particular risk given current estimates of global climate change. Yet, much uncertainty exists on the effects of climate shifts in ectothermic species from cool temperate regions, such as Patagonia. In this study we focus on the impact of environmental temperature on growth, age at sexual maturity and life-span of the Patagonian gecko Homonota darwinii. Skeletochronological methods were used to assess the bone growth rates of individuals from three populations at different geographic and temporal scales: two populations from Chubut (warm site; 1941 and 2010) and one population from Río Negro (cold site; 1997-1998). Populations displayed similar bone arrangement and growth patterns fit a von Bertalanffy curve. Three populations attained reproductive size at a minimum age of three years, but at the cold site two specimens were shown to mature in four years. We found no differences in juvenile growth rates in body size or bone zone width between juveniles of 1 to 3 years of age from the 1941 warm site and the 2010 warm site. But these traits appeared to be higher at these two warm sites than at the cold site which is consistent with the climatic differences among the three localities. Our results suggest that higher temperatures positively affect growth, denoting that global warming might benefit H. darwinii, especially the southern populations.